LACTIC ACIDOSIS AND TRANSAMINITIS IN A TYPE 1 DIABETES PATIENT WITH RECURRENT DIABETIC KETOACIDOSIS - L, Xe Hui; L, Shueh Lin (Journal of the ASEAN Federation of Endocrine Societies, 2019)
CASE We report an interesting case of a 16-year-old boy with type 1 diabetes mellitus, who had 14 admissions for diabetic ketoacidosis (DKA) since 2016. During many of his admissions for severe DKA, despite resolution of DKA and being clinically well, he continued to have lactic acidosis and markedly elevated aminotransferases. Lactic acidosis is a common finding in DKA, whereas glycogenic hepatopathy (GH) is a rare complication of poorly controlled diabetes mellitus characterised by transient liver dysfunction, elevated liver enzymes and associated hepatomegaly. Lactic acidosis in DKA is multifactorial in aetiology, from anaerobic glycolysis due to inadequate tissue perfusion and oxygenation, as well as metabolic derangements in DKA itself contributing to elevated lactate levels. On the other hand, the pathophysiology of GH is incompletely understood, and clinical characteristics have not been fully characterised. It is believed to be the consequence of recurrent fluctuations in glucose level with hyperglycaemia, hypoglycaemia and hyperinsulinization. CONCLUSION Awareness of the occurrence of lactic acidosis and glycogenic hepatopathy in patients with uncontrolled diabetes presenting with DKA should be increased among clinicians to guide further management appropriately. With this, we can increase our patient data pool to better understand patient characteristics and associated risk factors.